2021
DOI: 10.1038/s41598-021-86648-7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis identifies the effect of dietary multi-enzyme supplementation on gut health of pigs

Abstract: Gut health though is not well defined the role of gastrointestinal tract is vital if an animal must perform well. Apart from digestion, secretion, and absorption gut is harbored with consortium of microbiota which plays a key role in one’s health. Enzymes, one of the alternatives for antibiotics with beneficial effects on digestion and consistency of food and its effect on gut health. The effect of enzyme supplementation on gut health is not well established and the objective of this meta-analysis is to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Following exposure to pesticides, the liver and kidneys have been shown to exhibit a change in the vacuoles in the proximal tubules, causing necrosis and hepatocellular damage, respectively ( Eid, 2017 ; Lenz et al, 2018 ). Multi-enzyme may benefit more than single or two enzyme supplement to improving gut health ( Ramani et al, 2021 ). These changes can be observed within our study.…”
Section: Resultsmentioning
confidence: 99%
“…Following exposure to pesticides, the liver and kidneys have been shown to exhibit a change in the vacuoles in the proximal tubules, causing necrosis and hepatocellular damage, respectively ( Eid, 2017 ; Lenz et al, 2018 ). Multi-enzyme may benefit more than single or two enzyme supplement to improving gut health ( Ramani et al, 2021 ). These changes can be observed within our study.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to residual pesticides increased liver fibrosis and nonalcoholic fatty liver disease in HepG2 cells and rat liver ( Kwon et al, 2021a ; Kwon et al, 2021b ). Furthermore, meta-analysis revealed that the risk of idiopathic pulmonary fibrosis increased in agricultural workers exposed to pesticides ( Park et al, 2021 ; Ramani et al, 2021 ). Pesticide residues have a substantial influence on growth and health of livestock and humans ( Abou-donai, 2003 ; Cordes and Foster, 1988 ; Moses, 1989 ).…”
Section: Introductionmentioning
confidence: 99%